Changing the game: the case of cultural landscapes - Jacques, David (Protection of Cultural Heritage, 2023)
There are a number of thoughtful analyses on how the World Heritage Convention has progressed, notably by Jukka Jokelhito, and by Christina Cameron and Mechtild Rössler. They explain the principles on which the World Heritage Convention was based. It concerns the common heritage of the world’s most significant places – we would all be poorer if we lost them. This paper concerns the ideas we adopt in our dealings on landscape. The subject of cultural landscapes has been a latecomer in World Heritage terms. It is not a closely defined subject like, say, ecclesiastical architecture, and it has connections to many other subjects. Adjacent to many, it is defined by none. It still occupies a slightly detached column at the edge of the world heritage spreadsheet. It is not this paper’s intention to claim that the cultural landscapes community has been the initiator of fundamental ideas, but it has been touched by many from within and outside the World Heritage system, and in some cases has been instrumental in bringing about fresh thinking and change.